Unilateral Idiopathic Neuroretinitis Following Pfizer-BioNTech COVID-19 Vaccine; A Case Report (Global Journal of Medical Research, 2023)
This case report describes a temporal relationship of unilateral neuroretinitis following the second Pfizer-BioNTech COVID-19 Pfizer vaccine A 16-year-old male of mixed ethnicity presented with gradual loss of vision and pain on eye movement in his left eye 12 days after his second Pfizer vaccine His visual acuity in the left eye was count fingers at half a meter There was optic nerve head swelling macular exudates in a star-shaped pattern with peripapillary and foveal subretinal fluid consistent with left neuroretinitis His serological and radiologic investigations were negative for any alternative aetiology He was commenced on doxycycline rifampicin and oral prednisone on a tapering dose 4 months after presentation his left eye vision improved to 6 24-2 limited by loss to the outer retinal layers over the fovea The close proximity of the second Pfizer vaccine dose poses a temporal association with plausible causation
Keywords: neuroretinitis; COVID-19; SARS-CoV-2; Pfizer; New Zealand